1993
DOI: 10.1038/hdy.1993.172
|View full text |Cite
|
Sign up to set email alerts
|

Fertility estimates in the Tunisian all-acrocentric and Robertsonian populations of the house mouse and their chromosomal hybrids

Abstract: The reproductive features of wild all-acrocentric and 2n 22Robertsonian (Rb) house mice (M. m. domesticus) from Tunisia were studied. The aim was to examine the possibility of a reproductive selective advantage associated with chromosomal change as well as to measure the effect of heterozygosity for a large number of Rb fusions on the fertility of hybrids. Results showed that litter sizes were significantly smaller in Rb than in all-acrocentric mice. This difference, which may represent a favourable demographi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
50
2
7

Year Published

1999
1999
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(64 citation statements)
references
References 21 publications
4
50
2
7
Order By: Relevance
“…Segregation analysis on multiple heterozygous house mice for centric fusions are not frequent; however, data based on the karyotypical analysis of embryos derived from backcrossing of triple heterozygous males (White et al, 1978), although they are compatible with random segregation (as stated by the authors), fit better with a probability value of preferential segregation of 0.66 (95% confidence limits: 0.5-0.75); also the results of the karyotypical analysis of backcross progeny of heterozygotes for nine centric fusions (Said et al, 1993) are indicative, following our statistical analysis, of a preferential segregation (0.66 with 95% confidence limits: 0.56-0.71).…”
Section: Resultsmentioning
confidence: 89%
“…Segregation analysis on multiple heterozygous house mice for centric fusions are not frequent; however, data based on the karyotypical analysis of embryos derived from backcrossing of triple heterozygous males (White et al, 1978), although they are compatible with random segregation (as stated by the authors), fit better with a probability value of preferential segregation of 0.66 (95% confidence limits: 0.5-0.75); also the results of the karyotypical analysis of backcross progeny of heterozygotes for nine centric fusions (Said et al, 1993) are indicative, following our statistical analysis, of a preferential segregation (0.66 with 95% confidence limits: 0.56-0.71).…”
Section: Resultsmentioning
confidence: 89%
“…Therefore, these results indicate lower spermatogenic activity in Rb mice (heterozygotes and homozygotes) than in 40ST ones. Previous studies also reported a reduction in the tubular diameter in simple Rb heterozygote mice carrying nine fusions and in backcrosses of these hybrids with the parental races (Said et al 1993, Chatti et al 2005.…”
Section: Discussionmentioning
confidence: 98%
“…It has been demonstrated that house mice heterozygous for metacentrics have impaired reproductive fitness (for example, Wallace et al, 1992Wallace et al, , 2002Saïd et al, 1993;Hauffe and Searle, 1998), and that there are recombination effects in the vicinity of the centromere in such heterozygotes (for example, Davisson and Akeson, 1993;Bidau et al, 2001;Merico et al, 2003). Thus, one or both of these processes could affect gene flow in the centromeric region of the metacentric chromosomes investigated by us.…”
Section: Relationship Of Madeiran Metacentric Mice With Those Of Elsementioning
confidence: 99%